PENGARUH BUDAYA ORGANISASI, KARAKTERISTIK INDIVIDU DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN MOROWALI - Karim, Sadeli (Katalogis, 2016)
The objectives of this research are: 1) to determine and analyze positive and significant influence of organizational culture, individual characteristics, and communications on civil servants’ performance in The Agency of Disaster Management of Morowali Regency; 2) to determine and analyze the influence of organizational culture on civil servants’ performance, positively and significantly; 3) to determine and analyze the influence of individual characteristics on civil servants’ performance, positively and significantly; 4) to determine and analyze the influence of communications on civil servants’ performance, positively and significantly. The type of this research is causal descriptive to show the relationships between variables studied by involving 77 respondents who are selected through census method. Based on the test results, the study finds that: 1) organizational culture, individual characteristics, and communications simultaneously have positive and significant influence on civil servants’ performance in The Agency of Disaster Management of Morowali Regency; 2) organizational culture has positive and significant influence on civil servants performance; 3) individual characteristics has positive and significant influence on civil servants performance; 4) communications positively and significantly influence civil servants performance.